Makna Allah Pencipta Manusia dan Problematika Arti Kata ‘Kita’ dalam Kejadian 1:26-27 - Juliman Harefa (Sekolah Tinggi Teologi Torsina Surakarta, 2019)
This paper is an exegetical study of the book of Genesis 1:26-27, to understand whom God created, why God created a man who is called a noble creature, and studies the meaning of being pictured and similar to God. The study uses the hermeneutic spiral method (from text to context) to reveals the meaning of the original text of the Bible. Also, the implementation of the meaning of the original text today. The study of the text of the word Elohim, Yahweh/Adonay, and We contains the notions of the purity, omnipotence, majesty, and glory of the creator of the universe. The creator God created humans in His image and likeness so that humans have